2018
DOI: 10.1016/j.rasd.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

“Communicative skills in Spanish children with Autism Spectrum Disorder and children with Attention Deficit Hyperactivity Disorder. Analysis through parents’ perceptions and narrative production”

Abstract: Communicative skills in Spanish children with Autism Spectrum Disorder and children with Attention Deficit Hyperactivity Disorder. Analysis through parents' perceptions and narrative production 1. Introduction Recent studies have highlighted the diagnostic conundrum that clinicians often face when establishing differential diagnoses of verbally fluent school-age children with Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD) (Grzadzinski, Dick, Lord, & Bishop, 2016). These two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
1
8
0
1
Order By: Relevance
“…It should also be pointed out that although children with ADHD and TD children could not be distinguished based on parental rankings of morphosyntax in Helland et al (2012), children with ADHD did nonetheless demonstrate poorer performance on the morphosyntactic subscales than their TD peers, a pattern that also emerged in Geurts and Embrechts (2008). It is thus possible that children with ADHD demonstrate modest morphosyntactic difficulties, which would explain the results reported by Väisänen et al (2014) and Fortea et al (2018), but that these difficulties are not comparable in severity to those displayed by children with DLD.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…It should also be pointed out that although children with ADHD and TD children could not be distinguished based on parental rankings of morphosyntax in Helland et al (2012), children with ADHD did nonetheless demonstrate poorer performance on the morphosyntactic subscales than their TD peers, a pattern that also emerged in Geurts and Embrechts (2008). It is thus possible that children with ADHD demonstrate modest morphosyntactic difficulties, which would explain the results reported by Väisänen et al (2014) and Fortea et al (2018), but that these difficulties are not comparable in severity to those displayed by children with DLD.…”
Section: Introductionmentioning
confidence: 92%
“…It is also worth noting that several crosslinguistic studies have examined the morphosyntactic competences of schoolaged children with ADHD using Bishop's (2003) Children's Communication Checklist-Second Edition (see Fortea et al, 2018 for Spanish, Geurts and Embrechts, 2008for Dutch, Helland et al, 2012for Norwegian, and Väisänen et al, 2014 for Finnish). Again, findings are inconsistent as Väisänen et al (2014) and Fortea et al (2018) report morphosyntactic weakness for children with ADHD when compared to their TD peers, whereas children with ADHD could not be distinguished from the TD group in the studies by Geurts and Embrechts (2008) and Helland et al (2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some similarities in language abilities [25,37,38], various studies reported a wide variety of linguistic differences and impairments for children with ASD [39][40][41], particularly in the discursive and pragmatic aspects, in which various kinds of rules and processes govern the contextual suitability of language [42][43][44][45][46]. Some literature on referential choices made by children with ASD proposed that, due to impairments in attention, working memory, mental processes and difficulties in using pronouns, they tended to adhere their narratives to the explicit referential expressions such as full lexical noun phrases [18,47].…”
Section: Persian Referential Expressionsmentioning
confidence: 99%
“…This parental measure was designed for children between the ages 4 and 16 whose primary language is English. The CCC-2 contains 70 items grouped in 10 subscales measuring various aspects of communication: language (speech, syntax, semantics, coherence), pragmatics (inappropriate initiation, stereotyped language, the use of context, and non-verbal communication), and two scales assess the behaviors that are affected in children with ASD (social relationships and interests) (Fortea et al, 2018). In a study conducted by Timler (2014), significant correlations were found when the CCC-2 and the CELF-4 scores were compared, suggesting that the CCC-2 can accurately classify students with ADHD and concurrent LI.…”
Section: Introductionmentioning
confidence: 99%